The effect of mindfulness-based interventions on inattentive and hyperactive–impulsive behavior in childhood: A meta-analysis. (March 2021) - Vekety, Boglarka; Logemann, H. N. Alexander; Takacs, Zsofia K.
Current research has reported the beneficial effects of mindfulness-based interventions (MBIs) on general domains of cognition and behavior among children. The present study is the first meta-analysis with controlled studies investigating the pre-post change effects of MBIs on two widely experienced behaviors in childhood education, namely inattentiveness and hyperactivity–impulsivity. With a special developmental focus on the early years, a total of 21 studies with 3- to 12-year-old children were included in the meta-analysis. Results indicated that MBIs decreased children's overall inattentive and hyperactive–impulsive behavior with a small but significant effect size ( k = 21, g + = .38, p < .001). However, this overall positive effect was only significant when teachers rated children's behavior and nonsignificant when parents and children themselves were the informants. Additionally, MBIs showed a moderate effect in reducing inattentiveness and hyperactivity–impulsivity for children at risk for such behavior. In conclusion, results indicate that MBIs, which are relatively easily applied in educational practice, have the potential to decrease inattentive and hyperactive–impulsive behavior and might contribute to children's overall better functioning at school.